Językowe właściwości autora czy zecera w XVII-wiecznym tekście drukowanym ? - Pihan –Kijasowa, Alicja (Slavia Occidentalis, 2016)
17th-century printed texts, represented in the article by stylistically uniform texts of church sermons, mainly funeral sermons, are characterised by significant differences in the frequencies of specific forms entering into the composition of variant pairs or sequences. The completed research experiment consisted in the comparison of the frequency of individual variants. Firstly, in texts by a single author published in different printing offices in different cities, secondly, in texts by a single author published in different printing shops, but in the same city, and finally, in texts by various authors published in the same printing shop. The experiment demonstrated that, generally, the author of a printed text was not the one who made the selection of a specific word form constituting a part of a variant pair. We must note the significant contribution to this process of workers in the book industry employed in publishing offices: editors, proofreaders and type-setters. Usually, it is difficult to say that 17th- century printed texts were characterised by the originality of the language of their authors or proofreaders/ typesetters. A different attitude towards the problem would be more appropriate, acknowledging that we are dealing with linguistic properties of text which include some components of language used by the author-editor/proofreader – typesetter.